Registro del Programa de Sistemas Especiales de Importación-Exportación (Plan Vallejo Exprés) de la Empresa Technodetersa (2023)
The company Technodetersa S.A.S was founded in 2012, through a company by simplified shares through the capital of 3 shareholders. economic activity assigned to the company was wholesale trade in basic chemical products, rubbers and plastics in primary forms and chemical products for agricultural use and as secondary activity is the wholesale trade of other types of machinery and equipment N.C.P (Resolution 000139, Section G, 2012)